IMPROVEMENT IN HEART FAILURE NAVIGATOR CONSULTATION - A QUALITY IMPROVEMENT INITIATIVE - Parnia Abolhassan Choubdar, MD (Elsevier, 2024)
Therapeutic Area: Heart Failure Background: Heart failure (HF) has the highest 30-day rehospitalization rate among medical and surgical conditions. Data shows that HF patients who suffer from a 30-day readmission have worse prognosis at 6-month follow-up. Implementing educational interventions to improve outcome of adherence in HF patients has shown to reduce readmission rates by >15%. Although the means to implement such educational interventions are available, this resource appears grossly underutilized. Preliminary analysis showed that < 15% of patients admitted to advanced heart care with an ICD 10 diagnosis of acute heart failure exacerbation currently to receive an order for HF Navigator consultation. Methods: The number of heart failure navigator consults placed on the advanced heart care unit in relation to primary diagnosis of acute heart failure exacerbation was measured. The baseline, measured over several weeks prior to implementation of intervention, was measured to be <15%. Plan-Do-Study-Act (PDSA) Cycles were run. The cycles entailed: 1st Provider reeducation that ANY HF admission warrants HF Navigator consultation, 2nd Implementation of a widget making it accessible to follow up if consultation happened, 3rd order set for HF was enforced , which entailed the heart failure navigator order, 4th Distribution of reminder posters, post it's, and emails, 5th Distribution of questionnaire evaluating the main cause of lack of adherence to orders, serving as reminder to utilize the order, 6th educational meeting with the HF Navigator. 7th Information technology guided interventions are currently pending. Results: The following number of orders for heart failure navigator consultation were noted after each PDSA cycle:1st 16%, 2nd 16%, 3rd 33 %, 4th 39 %, 5th 26%, 6th 50% (Figure 1). Conclusions: Sustained and relevant change requires ongoing education, and improved workflow with utilization of order sets, which equal integrated clinical pathways. Ultimately, information technology support is needed to implement reflex orders, and clinical pathway tools, based on diagnosis, to ensure evidence based healthcare and optimal patient care. Advancements in electronic medical record systems with application of clinical pathways will improve human error and in the long-term safe patient suffering and hospital dollars.